Self-Presentational Cognitions for Exercise in Female Adolescents - Cumming, J.; Thogersen-Ntoumani, Cecilie (Wiley-Blackwell Publishing Inc., 2011)
The study's main purpose was to clarify the role of a range of self-presentational cognitions in the relationship between social physique anxiety and exercise behavior. Female participants (N= 331; M age = 14.5 years) reported their exercise frequency and completed measures of self-presentation. Exercise frequency was positively predicted by self-presentational efficacy expectations (SPEE) and self-presentational outcome value (SPOV). Moreover, SPEE moderated the relationship between social physique anxiety (SPA) and exercise frequency. SPA was negatively related to exercise frequency when SPEE was high, but positively related to exercise frequency when SPEE was low. Therefore, interventions designed to increase exercise frequency among adolescent girls should include strategies that both reduce SPA and enhance SPEE and SPOV.